A Comparative Study of the Safety and Efficacy of Amlodipine and Enalapril when Prescribed as Monotherapy in Patients with Isolated Systolic Hypertension - Yadav, Rajesh; Shah, Rekha (Journal of Nobel Medical College, 2023)
Background: Most elderly patients with high blood pressure have isolated systolic hypertension. Enalapril and amlodipine are respectively the most commonly prescribed ACE inhibitors and calcium channel blockers in Nepal. The goal of the current study was to compare the adverse drug reaction associated with amlodipine and enalapril in the study population as well as to compare the mean blood pressure and pulse rate reductions caused by amlodipine and enalapril in isolated systolic hypertensive patients.Materials and Methods: A comparative cross-sectional study was performed on 72 patients of both genders within the age group of 30 to 90 years; with isolated systolic hypertension; attending the out-patients department of Medicine of Nobel Medical College and Teaching Hospital; from December 2022 to February 2023. Mean reductions in systolic and diastolic blood pressure in the two treatment groups over the eight-weeks study period was calculated and then compared. Frequencies of patients developing different side effects was also calculated and compared between the two groups.Results: Systolic blood pressure was reduced by 16.1% in amlodipine group and by 18.8 % in enalapril group. Enalapril was slightly more efficacious in reducing the systolic blood pressure but such changes were found to be of no significant difference when compared between the two groups. (p > 0.05). The incidence of adverse effect was more in the amlodipine group in comparison to the enalapril group. Dry cough, dizziness, headache and fatigue with enalapril; and headache, peripheral edema, shortness of breath, fatigue, and flushing and dizziness with amlodipine were the common adverse effects.Conclusion: Both amlodipine and enalapril were equally effective in lowering systolic blood pressure without significantly lowering diastolic blood pressure. They were also generally well tolerated, though amlodipine was slightly more likely to cause side effects.